Detecting Presence of Chlamydia trachomatis in Donated Blood at Regional Blood Transfusion Centre, Eldoret, Kenya - Chemutai, P.; Ramesh, F.; Onyango, Frank K. (Recent Updates in Disease and Health Research Vol. 8, 2024)
Background and Aim: C. trachomatis is globally a major cause of sexually transmitted diseases (STDs) including Chlamydia. It causes various contaminations in donated blood. This study aims to detect Chlamydia trachomatis in donated blood at the Regional Blood Transfusion center, Eldoret, Kenya. Methodology: A random selection of blood samples was done for this study for a period of one month from July 24th 2017 to August 24th 2017. The prevalence of C. trachomatis was also determined with the help of the demographic questionnaire that is mandatory to be filled by the donor before any blood donation. Blood bags were numbered 1-87 and picked amongst unnumbered blood bags by each donor in order of donation. The samples obtained were subjected to centrifugation and serum used in the immunoassay test by using the Chlamydia trachomatis IgG/IgM Elisa test kit. Results: In this study, a greater percentage of the samples were from the donors between 20-29 years of age (60.9%), while the least was below 20 years old group. This study showed that C. trachomatis was present in 8% (7 samples) of the blood samples analyzed and 92% were found to be negative. The age group between 20 to 29 years old had the greatest percentage of those with C. trachomatis. Conclusion: With 8% of the samples testing positive for Chlamydia trachomatis this indicated that some of the blood donated to the Regional Transfusion Center is contaminated.